Glaucoma in high myopia and parapapillary delta zone - Jonas, Jost B. (PLOS ONE, 2017)
Purpose To examine the prevalence of glaucomatous optic neuropathy (GON) in a medium myopic to highly myopic group of patients and its association with parapapillary gamma zone and parapapillary delta zone. Methods The retrospective observational hospital-based study included patients who had attended the Tokyo High Myopia Clinics within January 2012 and December 2012 and for whom fundus photographs were available. GON was defined based on the appearance of the optic nerve head on the fundus photographs. Results The study included 519 eyes (262 individuals) with a mean age of 62.0±14.3 years (range:13-89 years) and mean axial length of 29.5±2.2 mm (range:23.2-35.3mm). GON was present in 141 (27.2%; 95% confidence intervals (CI): 23.3, 31.0%) eyes. Prevalence of GON increased from 12.2% (1.7, 22.7) in eyes with an axial length of <26.5mm to 28.5% (24.4, 32.5) in eyes with an axial length of ≥26.5mm, to 32.6% (27.9, 37.2) in eyes with an axial length of ≥28mm, to 36.0% (30.5, 41.4) in eyes with an axial length of ≥29mm, and GON prevalence increased to 42.1% (35.5, 48.8) in eyes with an axial length of ≥30mm. In multivariate analysis, higher GON prevalence was associated (Nagelkerke r2: 0.28) with larger parapapillary delta zone diameter (P<0.001; odds ratio (OR):1.86;95%CI:1.33,2.61), longer axial length (P<0.001;OR:1.45;95%CI:1.26,1.67) and older age (P = 0.01;OR:1.03;95%CI:1.01,1.05). If parapapillary delta zone width was replaced by the vertical disc diameter, higher GON prevalence was associated (r2:0.24) with larger vertical optic disc diameter (P = 0.04;OR:1.70;95%CI:1.03,2.81), after adjusting for longer axial length (P<0.001;OR:1.44;95%CI:1.26,1.64) and older age (P<0.001;OR:1.04;95%CI:1.02,1.06). Conclusions Axial elongation associated increase in GON prevalence (mean: 28.1% in a medium to highly myopic study population) was associated with parapapillary delta zone as surrogate for an elongated peripapillary scleral flange and with larger optic disc size.